Web-Based Recommender System for High School Major Decision Using Forward Chaining - Ira Wardani; Prima Dina Atika; Herlawati Herlawati (LPPM Universitas Islam 45 Bekasi, 2022)
Education is a learning process for students to develop their potential skills. One of the vocational schools is the State Vocational High School (SMK) 05 Bekasi, that educates students to have high expertise in industrial fields. However, not every student can choose the right major, there are students who choose majors based on the wishes of their parents, and do not know their real potential and abilities, so that the abilities of students are not in accordance with the majors they have chosen. One way that can be used to help choose the right major is to take a preference test that is assessed by a psychologist or the Counseling Guidance section. This method is quite effective, but it takes time especially for large numbers of student. Therefore, the researcher created a website-based recommendation system to identify majors using the Forward Chaining method. The purpose of the research is to make a recommendation system to determine the majors that students will choose. The application are developed using the System Development Life Cycle.